Anchoring Metal‐Organic Framework‐Derived ZnTe@C onto Elastic Ti3C2Tx MXene with 0D/2D Dual Confinement for Ultrastable Potassium‐Ion Storage. Issue 47 (26th October 2022) - Hu, Rongxiang; Sha, Dawei; Cao, Xin; Lu, Chengjie; Wei, Yicheng; Pan, Long; Sun, ZhengMing
Abstract: The prosperous deployments of renewable energy have stimulated the looming exploration of K‐ion batteries (KIBs) for grid‐scale energy storage because of their high energy density and low cost. However, lacking advanced anode materials with high theoretical capacity, fast K + storage kinetics, and eco‐friendliness discourages KIB development. Here, for the first time, ZnTe as an advanced KIB anode material with a conversion reaction mechanism ( y ZnTe + x K +  + x e −  → y Zn + K x Te y ) is demonstrated. The ZnTe nanoparticles are uniformly dispersed in a carbon matrix using metal–organic frameworks as starting materials, which are subsequently anchored on Ti3 C2 T x MXene nanosheets, forming elaborate ZnTe@C/Ti3 C2 T x (ZCT) nanohybrids. Various theoretical modeling and postmortem examinations reveal the synergistic integrations between carbon and Ti3 C2 T x . Compositionally, they regulate the electronic structure of ZnTe, providing fast K + adsorption kinetics. Morphologically, they construct a 0D/2D dual confinement, addressing the volume change of ZnTe upon cycling. Therefore, the ZCT exhibits a high capacity (408.0 mA h g −1 at 0.1 A g −1 ) and excellent long‐term cyclability (230.2 mA h g −1 at 1.0 A g −1 after 3500 cycles), outperforming other reported transition‐metal‐chalcogenides. Significantly, the ZCT‐based full cells achieve a high energy density of 110.3 Wh Kg −1, making ZCT promising for practical applications. Abstract : This work has demonstrated ZnTe as an advanced conversion‐type anode material for K‐ion batteries. By integrating 0D carbon coating and 2D Ti3 C2 T x MXene, a dual confinement is constructed to address the volume change of ZnTe upon cycling. The resulted ZnTe@C/Ti3 C2 T x nanohybrids show excellent cyclability in half cells and high energy density in full cells, making it promising for practical applications.